Enhancer of zeste homolog 2 regulates cell differentiation and proliferation in neuroblastoma - Amallia N. Setyawati; Takehiko Kamijo (Faculty of Medicine, Universitas Trisakti, 2014)
BACKGROUNDNeuroblastoma (NB) is one of the most common extracranial solid tumorsoccurring in infancy and childhood with highly variable outcomes. Polycombgroup (PcG) proteins are epigenetic gene silencers. Enhancer of zeste homolog2 (EZH2) is a member of the polycomb repressor complex 2 (PRC2) group,with the main function to catalyze the polycomb repressor complex bymethylating lysine 9 and 27 of histone H3. This study aimed to investigate thebiological functionality of EZH2 in NB. METHODSThis was an experimental study with an analysis of correlation initially of theknown prognostic factors of NB patients’ outcomes, by comparing the expressionof v-myc avian myelocytomatosis viral oncogene neuroblastoma (MYCN) withthat of EZH2, on the basis of the patients’ overall and relapse free survivalrates. This was followed with a biological functional study to assess the role ofEZH2 expression in NB. RESULTSEZH2 knockdown induces neurite extension and differentiation marker growthassociated protein 43 (GAP43) in NB cells, although it does not affect cellcycle. By ectopic expression of EZH2, all-trans retinoic acid (ATRA) inducedneurite extension was suppressed and GAP43 was decreased. Overall, EZH2seems to have an important role in NB cell differentiation. Although EZH2 didnot alter cell proliferation, in the soft agar colony formation assay there was asignificant increase in total colony number and number of large colonies. CONCLUSIONOur result clarified the potential role of EZH2 in the regulation of celldifferentiation and proliferation, which subsequently may play an importantrole in the poor prognosis of NB patients.